Strategy comparison of TikTok as political campaign platform of Partai Islam Se-Malaysia (PAS) and Partai Keadilan Sejahtera (PKS) - Krisdian, David; Almushaf, Hasby Affan; Hamzah, Helmi Fikrilmi; Samuel, Hanzel; Djuyandi, Yusa; Abdul Wahab, Shafezah (Faculty of Communication & Media Studies, 2024)
The Ikhwanul Muslimin movement that started in 1928 in Egypt has brought a change in the political science as well as the political condition of a lot of muslim countries in the world. Indonesia and Malaysia, which are notorious for being one of the biggest muslim countries in the world, are also the ones that are affected by the growing Ikhwanul Muslimin movement. The movement in the end created a political power which created political parties with an ideology and orientation to the values that Ikhwanul Muslimin holds. In contemporary periods, in Indonesia and Malaysia there are political parties that derived from the Ikhwanul Muslimin movement which is the Partai Islam Se-Malaysia (PAS) and Partai Keadilan Sejahtera (PKS). The study case is trying to compare how the two parties which derive from the same movement do its campaign to win the elections in both countries.